Utilization of Camtasia Application for Learning Media in Natural Science Subjects at Elementary School - Ginarti Ginarti; Surya Hidayat; Iwan Harsono (Journal of Social Science Utilizing Technology, 2023)
Background. During the COVID-19 period, all levels of life were severely disrupted, including the world of education, many educational institutions and governments decided to temporarily close their institutions such as schools and campuses. The COVID-19 pandemic requires the teaching and learning process to be carried out at a distance, this requires teachers to be able to take advantage of technological developments that exist today to help the learning process. Purpose. The purpose of this research is to create lesson media for students so that lessons become more interesting and students are more enthusiastic in learning. Method. This article uses descriptive qualitative research methods and meta-analysis. Qualitative descriptive is a process of providing a comprehensive description of a problem that develops with a creative idea that will be used as an innovative solution Results. The result of this study is that the utilization of learning video media at State Elementary School 05 Sembilan Koto in Sembilan Koto sub-district, Dharmasraya Regency is very effective due to an increase in learning outcomes and the quality of education in the Elementary School. One example that can be taken is in the subject of Natural Sciences, where previously student scores at the 05 Sembilan Koto State Elementary School were initially low due to the impact of the COVID-19 pandemic. But after using Camtasia learning videos, the value of learning Natural Sciences increased. Conclusion. Based on research and data from the results of the study, it can be concluded that providing material using a new media and in accordance with the development of the times is very necessary.